Implementasi Modul Ajar Pendidikan Agama Islam dalam Pembentukan Profil Pelajar Pancasila di SMP Negeri 2 Majene - Muh. Muhyiddin R. Mahmud; Muhammad Saleh; Agus Muchsin; Sitti Jamilah Amin; Muzakkir Muzakkir (Departement of Mathematics Education, 2024)
This study aims to understand and analyze the implementation of Pendidikan Agama Islam (PAI) or Islamic Education teaching modules in shaping the profile of Pancasila students at SMP Negeri 2 Majene. Using a qualitative research method with a descriptive approach, data were collected through in-depth interviews, observations, and documentation. The results indicate that the implementation of the PAI teaching module at SMP Negeri 2 Majene has been effective in shaping the profile of Pancasila students. This teaching module integrates Pancasila values into the learning material, aiding students in understanding and practicing these values in their daily lives. Key factors supporting the successful implementation of the PAI teaching module include strong school support, high-quality teaching modules, and the commitment of teachers to teach and instill Pancasila values. However, some challenges were identified, such as limited instructional time and insufficient parental involvement in the value education process. The study concludes that the PAI teaching module significantly contributes to shaping the profile of Pancasila students at SMP Negeri 2 Majene. Recommendations include enhancing the quality of training for PAI teachers, strengthening collaboration between schools and parents, and developing more interactive and contextually relevant teaching modules that align with contemporary developments.